Occurrence of Bacterial Pathogens and Human Noroviruses in Shellfish-Harvesting Areas and Their Catchments in France - Rincé, Alain; Balière, Charlotte; Hervio-Heath, Dominique; Cozien, Joëlle; Lozach, Solen; Parnaudeau, Sylvain; Le Guyader, Françoise S.; Le Hello, Simon; Giard, Jean-Christophe; Sauvageot, Nicolas; Benachour, Abdellah; Strubbia, Sofia; et al. (Frontiers in Microbiology, 2018)
During a 2-year study, the presence of human pathogenic bacteria and noroviruses was investigated in shellfish, seawater and/or surface sediments collected from three French coastal shellfish-harvesting areas as well as in freshwaters from the corresponding upstream catchments. Bacteria isolated from these samples were further analyzed. E. coli isolates classified into the phylogenetic groups B2, or D and enterococci from E. faecalis and E. faecium species were tested for the presence of virulence genes and for antimicrobial susceptibility. Salmonella members were serotyped and the most abundant serovars (Typhimurium and its monophasic variants and Mbandaka) were genetically characterized by high discriminative subtyping methods. Campylobacter and Vibrio were identified at the species level, and haemolysin-producing V. parahaemolyticus were searched by tdh- and trh- gene detection. Main results showed a low prevalence of Salmonella in shellfish samples where only members of S. Mbandaka were found. Campylobacter were more frequently isolated than Salmonella and a different distribution of Campylobacter species was observed in shellfish compared to rivers, strongly suggesting possible additional inputs of bacteria. Statistical associations between enteric bacteria, human noroviruses (HuNoVs) and concentration of faecal indicator bacteria revealed that the presence of Salmonella was correlated with that of C. jejuni and/or C. coli as well as to E. coli concentration. A positive correlation was also found between the presence of C. lari and the detection of HuNoVs. This study highlights the importance of simultaneous detection and characterization of enteric and marine pathogenic bacteria and human noroviruses not only in shellfish but also in catchment waters for a hazard assessment associated with microbial contamination of shellfish.